The Present Situation in the Mining Industry of New Brunswick - W. J. Wright (Canadian Institute of Mining, Metallurgy and Petroleum, 1931)
Summary This paper describes the general situation of the mining industry in New Brunswick, and gives a detailed description of the recent developments in the antimony deposits at Lake George and the copper deposits in the vicinity of New Horton. At the end are lists of the most interesting geological literature relating to the Province and of the geological and topographic maps that have been published. Introduction In presenting this paper to the Institute, I apologize for the small amount of scientific data which it contains. Recent investigations in the Province of New Brunswick have been carried on largely by outside interests, and at present we ourselves are in the position .of taking stock. However, I am glad of the opportunity of giving you a general idea of the situation. The Province is making an honest effort to learn the truth concerning her mineral deposits and in time hopes to collect data which should be of interest to the mining community.